2003
DOI: 10.1007/s11745-003-1070-4
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption and blood lipids in three ethinic groups of Québec (canada)

Abstract: The purpose of this study was to compare fish intake and plasma phospholipid concentrations of n-3 fatty acids, in particular of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), among representative population samples of Québecers, James Bay Cree, and Inuit of Nunavik (Canada). The relationships between these concentrations and cardiovascular disease (CVD) risk factors were also investigated and compared in the three populations. In 1990-1992, the study subjects had participated in the extensive San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 37 publications
3
42
1
1
Order By: Relevance
“…This correlation has been widely studied in phospholipid fatty acids (Dewailly et al, 2003;Laidlaw and Holub, 2003;Mozaffarian et al, 2005) but little information has still been reported for total fatty acids. A recent study conducted in Japan, one of the areas with the highest fish consumption in the world, examined the association between the intake frequency of fish with longchain n-3 fatty acids in serum of 1257 subjects (Wakai et al, 2005) and the calculated coefficients of correlation were lower than the found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation has been widely studied in phospholipid fatty acids (Dewailly et al, 2003;Laidlaw and Holub, 2003;Mozaffarian et al, 2005) but little information has still been reported for total fatty acids. A recent study conducted in Japan, one of the areas with the highest fish consumption in the world, examined the association between the intake frequency of fish with longchain n-3 fatty acids in serum of 1257 subjects (Wakai et al, 2005) and the calculated coefficients of correlation were lower than the found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…If you quit smoking, then your HDL-C can increase up to 15% to 20%, an elevation on par with some of the best drugs available for raising HDL-C. Increased fish 7 and reduced carbohydrate consumption both are associated with higher HDL-C. The so-called Mediterranean diet (a diet enriched with fruits, vegetables, whole grains, olive oil, and legumes) is associated with increased HDL-C. 8 Alcohol consumption can raise HDL-C significantly, 6 but this benefit must be counterbalanced with knowledge of the risks of alcohol consumption.…”
Section: Lifestyle Modification and Hdl-cmentioning
confidence: 99%
“…A diet rich in Inuit traditional food is thought to protect from cardiovascular disease and diabetes due to relatively high levels of n-3, mono and polyunsaturated fatty acids and low levels of n-6 fatty acids (2)(3)(4)(5)(6)(7). Other dietary characteristics include high intakes of antioxidants, vitamins, micronutrients and phytochemicals (2,(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%